Effectiveness of Career Guidance Information Service on The Educational Aspiration Level of The Students - Arsyad Arsyad (Jurnal Dakwah Risalah, 2015)
Career guidance information service is given to the students to provide them with knowledge about career or further education. This would help the students to plan their future after graduating from high school. When the students were not provided with career guidance information service, they would be confused to continue their study, have lack of understanding on their interest and talent, be unable to develop their potential and have low willingness to continue their study. This research was designed for revealing the effectiveness of career guidance information service to improve the students’ educational aspiration level in class X of SMK Muhammadiyah 1 Pekanbaru in Academic Year 2013/2014. The sample of this research was 30 students. The sample was taken by using purposive sampling technique. This research applied pre-experimental technique and Pre-Test and Post-Test One Group Design. The data was collected through the educational aspiration scale. The data gotten was analyzed by using percentage descriptive analysis and quantitative analysis with t-test. The result of the research indicated that the students’ educational aspiration level in class X of SMK Muhammadiyah 1 Pekanbaru was low (0%), but then it became higher (50%) after career guidance information service given. The result of the research indicated that career guidance information service given was effective to improve the students’ educational aspiration level.